THE SIGNIFICANCE OF THE KLOTHO PROTEIN AT THE EARLY STAGE OF DIABETIC NEPHROPATHY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Klotho is being investigated for its potential as a biomarker for the early diagnosis of diabetic nephropathy in patients with type 2 diabetes . Early detection of diabetic nephropathy is very important to prevent or slow down the progression of kidney damage. Klotho should be studied as a potential biomarker for early diagnosis and risk stratification of diabetic nephropathy.